Modern Social and Cultural Anthropology (Main Trends and Currents) - Gendrolis, Edmundas (Problemos, 1976)
The characteristic feature of the social and cultural anthropology in the first half of the 20th century is that, instead of reconstructing the history of society, it investigates the extant illiterate or preindustrial societies, the institutional aspects of their culture. The paper discusses the following questions: the place and role of the social and cultural anthropology in the system of social sciences; the common and different views of these sciences on the object of investigation; the development of these sciences from evolutionism to functionalism in Britain and to neo-evolutionism in the USA. In this connection the theoretical views of the English functionalists' and representatives of the US cultural anthropology are presented in brief. Methods of investigation suggested by the representatives of these trends are scientifically valid when applied to separate societies. But inherent in them empiricism and particularism, resulting from the positivist methodology, did not allow to determine general regularities in the development of the preclass society at large.